How different attributes are weighted in professionals' decision-making in Pediatric Dentistry-a protocol for guiding discrete choice experiment focused on shortening the evidence-based practice implementation for dental care - Gabriela Manco Machado; Ana Clara Falabello Luca; Renata Paz Leal Pereira; Ana Yne Fernandez; Lucas Gabriel Santini Rodrigues; Isabella Petroline Leite; Maximiliano Sergio Cenci; Tatiana Pereira Cenci; Ana Paula Pires Santos; Branca Heloisa Oliveira; Paulo Nadanovsky; Marina Deus Moura Lima; et al. (BMC, 2024)
Abstract Background Important evidence has been constantly produced and needs to be converted into practice. Professional consumption of such evidence may be a barrier to its implementation. Then, effective implementation of evidence-based interventions in clinical practice leans on the understanding of how professionals value attributes when choosing between options for dental care, permitting to guide this implementation process by maximizing strengthens and minimizing barriers related to that. Methods This is part of a broader project investigating the potential of incorporating scientific evidence into clinical practice and public policy recommendations and guidelines, identifying strengths and barriers in such an implementation process. The present research protocol comprises a Discrete Choice Experiment (DCE) from the Brazilian oral health professionals' perspective, aiming to assess how different factors are associated with professional decision-making in dental care, including the role of scientific evidence. Different choice sets will be developed, either focusing on understanding the role of scientific evidence in the professional decision-making process or on understanding specific attributes associated with different interventions recently tested in randomized clinical trials and available as newly produced scientific evidence to be used in clinical practice. Discussion Translating research into practice usually requires time and effort. Shortening this process may be useful for faster incorporation into clinical practice and beneficial to the population. Understanding the context and professionals' decision-making preferences is crucial to designing more effective implementation and/or educational initiatives. Ultimately, we expect to design an efficient implementation strategy that overcomes threats and potential opportunities identified during the DCEs, creating a customized structure for dental professionals. Trial registration https://osf.io/bhncv .